Management strategies for adult patients with dental anxiety in the dental clinic: a systematic review. (12th July 2022) - Hoffmann, B; Erwood, K; Ncomanzi, S; Fischer, V; O'Brien, D; Lee, A
Abstract: Anxiety is an adaptive emotional response to potentially threatening or dangerous situations; moderated by the sympathetic nervous system. Dental anxiety is common and presents before, during or after dental treatment. The physiological response includes an increase in heart rate, blood pressure, respiratory rate, and cardiac output. Consequently, extensive distress leads to avoidance of dental treatment and multiple failed appointments, impacting both oral and general health. Dental anxiety can generate a variety of negative consequences for both the dentist and the patient. Evidence‐based strategies are essential for mitigating and relieving anxiety in the dental clinic. Psychotherapeutic behavioural strategies can modify the patient's experience through a minimally invasive approach with nil or negligible side effects, depending on patient characteristics, anxiety level and clinical situations. These therapies involve muscle relaxation, guided imagery, physiological monitoring, utilizing biofeedback, hypnosis, acupuncture, distraction and desensitization. Pharmacological intervention utilizes either relative analgesia (nitrous oxide), conscious intravenous sedation or oral sedation, which can have undesirable side effects, risks and contraindications. These modalities increase the cost and availability of dental treatment.